2010
DOI: 10.1128/jvi.02281-09
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Duck Hepatitis B Virus Infection Requires Cleavage by a Furin-Like Protease

Abstract: The entry mechanism of hepatitis B virus (HBV) has not been defined, and this impedes development of antiviral therapies aimed at an early step in the viral life cycle. HBV infection has both host and tissue specificities. For the related duck hepatitis B virus (DHBV), duck carboxypeptidase D (DCPD) has been proposed as the species-specific docking receptor, while glycine decarboxylase (DGD) may serve as a tissuespecific cofactor or secondary receptor. DGD binds to several truncated versions of the viral large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…The initial steps during DHBV infection in vitro involve virus binding to the hepatocyte surface via the pre-S region of the large envelope protein. Duck carboxypeptidase D and glycine decarboxylase have been proposed as virus receptor molecules, and uptake of virus is thought to occur by receptor-mediated endocytosis, with cleavage of the DHBV envelope protein by a furin-like protease (24) and virus entry into early endosomes (25). Although many details of the intracellular pathways involved have not yet been determined, it has been hypothesized that the virus envelope fuses with the endosome to allow delivery of the virus nucleocapsid to the cytoplasm.…”
mentioning
confidence: 99%
“…The initial steps during DHBV infection in vitro involve virus binding to the hepatocyte surface via the pre-S region of the large envelope protein. Duck carboxypeptidase D and glycine decarboxylase have been proposed as virus receptor molecules, and uptake of virus is thought to occur by receptor-mediated endocytosis, with cleavage of the DHBV envelope protein by a furin-like protease (24) and virus entry into early endosomes (25). Although many details of the intracellular pathways involved have not yet been determined, it has been hypothesized that the virus envelope fuses with the endosome to allow delivery of the virus nucleocapsid to the cytoplasm.…”
mentioning
confidence: 99%
“… 16 We found that dCPD mediated DHBV binding/endocytosis is followed by rapid viral exit, which could be minimized by co-transfection of chicken furin. 17 dCPD, p120, and DHBV L protein colocalized in endosomal fraction, and endosomal enzymes could cleave the L protein on DHBV particles. 17 Incubation of chicken hepatoma cell line LMH with such cleaved DHBV particles generated small amount of cccDNA.…”
Section: Does Dhbv Entry Require Proteolytic Cleavage Of Its L Proteimentioning
confidence: 94%
“… 17 dCPD, p120, and DHBV L protein colocalized in endosomal fraction, and endosomal enzymes could cleave the L protein on DHBV particles. 17 Incubation of chicken hepatoma cell line LMH with such cleaved DHBV particles generated small amount of cccDNA. Finally, a furin inhibitor capable of blocking L protein cleavage by purified endosomal fraction could also inhibit DHBV infection of duck hepatocytes.…”
Section: Does Dhbv Entry Require Proteolytic Cleavage Of Its L Proteimentioning
confidence: 94%
“…The 2 kb LAT is not capped or poly-adenylated because it is a stable intron (Farrell et al, 1991; Krummenacher and Zabolotny, 1997). The LAT locus also encodes numerous micro-RNAs (miRNA) (Cui et al, 2006; Jurak et al, 2010; Umbach et al, 2008, 2009). Two small non-coding RNAs, 62 nt and 36 nt long, are expressed from the first 1.5 kb of LAT coding sequences (LAT sncRNA1 and sncRNA2) (Peng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…LAT sncRNA1 and sncRNA2 are not miRNAs because the mature miRNA band that migrates between 21 and 23 nucleotides is not detected, they lack certain structural features of miRNAs, and both sncRNAs have the potential to form complex secondary structures. It is unlikely that LAT sncRNA1 and sncRNA2 were detected using procedures described for the HSV-1 encoded LAT miRNAs (Jurak et al, 2010; Umbach et al, 2008) because RNA species migrating between 17 and 30 nucleotides were size selected and then deep-sequencing performed.…”
Section: Introductionmentioning
confidence: 99%